KKN Tematik UPI 2023: Persepsi Masyarakat Terkait Stunting di Kelurahan Pataruman, Kecamatan Pataruman, Kota Banjar, Jawa Barat - Hanifa, Eisha Sabila Dieni (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2024)
Stunting is a significant public health problem in many developing countries, including Indonesia. It is a condition where children have insufficient height for their age due to chronic malnutrition and inadequate access to essential nutrients. Stunting not only affects physical growth but also hampers cognitive development and overall well-being. To address this issue, this research aims to explore and analyse the perspectives of the local community in relation to stunting in Pataruman Village, Pataruman District, Banjar City, West Java. Participants in this qualitative research using a phenomenological approach were five mothers with children under the age of five who were interviewed comprehensively, which would later be reduced and presented descriptively. The results showed that even though the people of Pataruman Village already knew what stunting was, further counselling by local health workers was still needed for fast and appropriate prevention and treatment.